PESANTREN BERBASIS QUR'ANY : Penguatan Pendidikan Karakter dalam Menghadapi Arus Global - Sunardi, Sunardi; Munfarida, Isah (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2024)
Qur'ani-based Islamic boarding schools have a strategic role in facing global flows by strengthening character education. This research discusses the theoretical basis, learning methods, and the impact of Qur'ani-based Islamic boarding schools on student character development. This Islamic boarding school not only maintains traditional Islamic values, but also integrates technology and innovation in its learning approach. This research is library research where data is collected through books, articles and relevant ones used as references. Meanwhile, data analysts are used according to the researcher's abilities and understanding of the data found. Islamic boarding schools contribute positively to the formation of students' personality, ethics and tolerance. Despite facing challenges such as adapting to technology and meeting national standards, Qur'ani-based Islamic boarding schools also have the opportunity to become centers of authentic Islamic understanding in providing solutions to global challenges. This research is expected to enrich understanding of the role of Qur'ani-based Islamic boarding schools in strengthening character in the global era, as well as stimulate cooperation between Islamic boarding schools, government and society to produce a generation that is morally and ethically strong in facing global dynamics